Automimicry destabilizes aposematism: predator sample-and-reject behaviour may provide a solution. - Gamberale-Stille, G; Guilford, T (2004)
Aposematism, the use of conspicuous colours to advertise unpalatability to predators, is perhaps the most studied signalling system in nature. However, its evolutionary stability remains paradoxical. The paradox is illustrated by the problem of automimicry. Automimics are palatable individuals within a population of unpalatable aposematics. Automimics benefit from predators avoiding warning coloration without carrying the models' cost of unpalatability, and should increase in the population, destabilizing the signalling system, unless selected against in some way. Cautious sampling, instead of avoidance, by predators may offer a solution to this problem. Here, we investigate the effect of automimic frequency on predator sampling behaviour, and whether predator sampling behaviour may provide a selection pressure against mimics. Domestic chicks (Gallus gallus domesticus) were subjected to the task of discriminating between green (signalling) and untreated brown chick crumbs. Some of the green crumbs were quinine treated and thus unpalatable. The frequency of palatable signalling prey items varied in four treatments; all unpalatable, low automimic frequency, high automimic frequency and all palatable. The results show that predator sampling behaviour is sensitive to automimic frequency and that predators may discriminate between models and mimics through sampling, and thereby benefit unprofitable prey. The results suggest somewhat surprisingly that aposematic signalling is stable only because of the actions of those predators not actually deterred by warning signals.